Kontroversi Metode Deteksi COVID-19 di Indonesia - Mariana Wahjudi (Direktorat Penerbitan dan Publikasi Ilmiah Universitas Surabaya, 2020)
Abstract—The governance of COVID-19 cases in Indonesia is carried out in accordance with the WHO directions. Serological tests, often mentioned as rapid antibody tests, are used for mass screening testing while the polymerase-chain-reaction (PCR)-based tests are performed for routine confirmation of COVID-19 infection cases. PCR test is one of nucleic acid amplification tests (NAAT) for detection of viral RNA. The management of the COVID-19 detection caused controversies at the beginning of pandemic period. It seems that the controversies occurred due to misperception regarding the tests, as well as misunderstanding caused by differences in individual immune responses, viral dynamics in human bodies and clinical outcomes. In response to community opinion controversies, this paper discuss the following topics, i.e. a glimpse about COVID-19, the characteristics of SARS-CoV-2, viral dynamics in human body, the dynamics of human immune response to SARS-CoV-2, basic explanation about COVID-19 and SARS-CoV-2 testing, and the last part explained the occurred controversies. Keywords: Indonesia, polymerase chain reaction, rapid test, SARS-CoV-2, serology